Substance Use and Mental Health Effects of Disrupting Treatment and Shelter Services on Boston Harbor's Long Island - Laura C. Ha; Karen T. Foo; Hannah L. Harp; Leslie R. Brody; Mardge H. Cohen (Social Medicine Publication Group, 2020)
Objective: To understand the impact of Boston's October 2014 Long Island Bridge Closure. Methods: We conducted a qualitative analysis of semi-structured interviews with nine individuals displaced from programs on the Island. Participants were recruited and interviewed during March and April of 2015. Interviewers administered a 22-item questionnaire and a semi-structured interview at the temporary shelters and programs at South End Fitness Center, BHCHP, Woods-Mullen Shelter, and Shattuck Hospital. Thematic analysis of the transcribed interview data was conducted using an inductive framework approach. Results: Thematic analysis of the interviews revealed that the most prominent ramifications of the bridge closure were worsening of mental health, substance use behavior, and housing insecurity. Further analysis revealed the importance of stable housing in maintaining sobriety and mental health. Conclusions: When medical and social services for vulnerable populations are at risk of closure, careful planning, quick mobilization of resources, and investment in affordable housing, are crucial in preventing adverse mental health outcomes. Maintaining shelter and substance use treatment programs should be a high priority, even when government funding is at risk.